HistoGreen: a new alternative to 3,3′-diaminobenzidine-tetrahydrochloride-dihydrate (DAB) as a peroxidase substrate in immunohistochemistry? - Thomas, Martin Alexander; Lemmer, Björn (Brain research. Brain research protocols, 2005)
Abide its toxicity, 3,3′-diaminobenzidine-tetrahydrochloride-dihydrate (DAB) was the most potent marker for immunochemistry at the light and electron microscopic level in the last decades. Recently, a sensitive substrate for immunohistochemical staining methods and in-situ hybridization, HistoGreen, was developed for the use with peroxidase. In peroxidase reactions, HistoGreen delivers a green staining product which is suitable for permanent embedding without water. In contrast to DAB, HistoGreen is not toxic. To evaluate its usefulness, we performed comparative immunohistochemistry on angiotensin II (AT1)-receptors with DAB- and HistoGreen-staining on paraffin embedded slices of the rat brain at the light microscopic level. This also included counterstaining with Mayer's Hemalum and Nuclear Fast Red, respectively. We could demonstrate that HistoGreen delivers a coarsely grained label which is fast detectable in light microscopy. HistoGreen equals DAB in the exact localization of the immunoreaction to a large degree but its reaction product is considerably less stable in alcohol and water than DAB. In combination with Nuclear Fast Red, HistoGreen provides excellent imaging properties for the visualization and documentation of immunoreactive structures paired with an adequate demonstration of cellular details. Its tendency towards rapid over-staining as well as its low stability will restrict the use of HistoGreen in some areas of immunohistochemical research, yet the new chromogen represents an interesting alternative to DAB at the light microscopic level.